PEMBERDAYAAN UMKM MAK PESEK: WARUNG TRADISIONAL YANG BERTRANSFORMASI DENGAN BRANDING DI SWK DUKUH MENANGGAL - Saputri, Arnaning Tias; Shofiyanti, Bintang Majida; Adedarma, Elok; Salsabila, Rania; Agustin, Aprilia Nisa Riswanda; Kristiyanti , Septi Dwi; Agustina, Tri Siwi; Hardi, John; Fitdiarini, Noorlaily; Sudarwito, Gurun (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2024)
This report presents the results of an analysis of the MSME "Warung Mak Pesek." Warung Mak Pesek is a culinary business that offers various types of homemade food at the Dukuh Menanggal Culinary Tourism Center. The study aims to analyze the internal and external conditions of the MSME, identify its opportunities and challenges, and provide recommendations to enhance its competitiveness and business sustainability. The research method used in this study is qualitative, with data collection techniques including observation and interviews with the head of the Dukuh Menanggal Culinary Tourism Center, the owner, and employees of "Warung Mak Pesek." Primary data were collected through direct observation at the business location, while secondary data were obtained from previous reports. The results indicate that "Warung Mak Pesek" has products favored by customers at affordable prices but has weaknesses in product marketing and financial management. Many other stalls offer similar products, but Mrs. Sumirah, the owner of "Warung Mak Pesek," has loyal and regular customers. Based on the research results, several development strategies are proposed, including enhancing online marketing strategies, implementing a financial recording system, redesigning a more attractive banner, and providing recommendations for other raw material suppliers. The implementation of these strategies is expected to help "Warung Mak Pesek" achieve sustainable growth. Keyword: MSME, Culinary, Development, Analysis, Business Strategy